Along Ecological Lines. Contemporary art and climate crisis. - Drabble, Barbnaby; Bresch, David; Demos, T.J.; Garcia-Dory, Fernando; Kagan, Sacha; Maeder, Eric; Phillips, Andrea; Ressler, Oliver; Schmidlin, Laurence; Umolu, Yesomi; édhea ([S.l.] : Gaia Project Press, 2019)
Biemann, Ursula ; Haley, David ; Velardi, Marie
hedendaagse kunst en ecologie
boek